Roles of student society and concept of service at university - Abdullah, Nurmuslimah Kamilah; Sulong @ A. Rashid, Ruzaidah; Muhammad Khodri Harahap, Afif Zuhri (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2024)
Tertiary education, also known as higher education or post-secondary education, refers to the stage of education that follows the completion of secondary school. This level of education typically includes universities, colleges, and vocational schools where students can pursue various undergraduate and graduate degrees, such as bachelor's degrees, master's degrees, and doctoral degrees. Usually, undergraduate students are encouraged to get involved with student clubs or societies on top of courses to be enrolled for every semester and pass with flying colours.